The effect of the Kasuya CKD network on prevention of the progression of chronic kidney disease: successful collaboration of a public health service, primary care physicians and nephrologists—community based cohort study - Katafuchi, Ritsuko; Tanaka, Shigeru; Matsuo, Takayuki; Tamai, Osamu; Yoshimine, Kazuhiro; Yano, Kazutoshi; Ueno, Kiichiro; Shimohashi, Naoya; Ninomiya, Toshiharu (Clinical and experimental nephrology, 2023)
Background In 2012, we established a CKD network in collaboration with the public health service, primary care physicians, and nephrologists in the Kasuya area. The aim of this study was to clarify if our CKD network was effective in preventing CKD progression. Methods 1591 subjects, who had CKD in health checks in 2012 were included in this study. The slope of estimated glomerular filtration rate (eGFR) was compared before and after 2012. Parameters at the first health check visit before 2012, visit in 2012, and the last visit after 2012, were compared. Paired t test, analysis of variance for repeated measurements, and the Friedman test were used for the analysis. Results Mean age was 65 years. There were 781 men and 810 women. Mean eGFR was 59 ml/min/1.73 m 2 . The mean slope of eGFR before 2012 was −1.833 ml/min/1.73 m 2 /year and significantly reduced to − 0.297 after 2012. Low-density lipoprotein cholesterol showed a significant serial lowering. Uric acid was significantly elevated in 2012 compared to the first visit and had decreased by the last. The dipstick urinary protein significantly increased in 2012 compared to the first visit and decreased by the last. The number of current smokers showed a significant reduction over time. On the other hand, systolic blood pressure (SBP) and HbA1c significantly elevated at the last visit. Conclusion The Kasuya CKD network may be effective in preventing CKD progression.